(untitled) - CLARA AYU CARRERA, HANA (LATERNE, 2012)
Speaking is one of four skill that should be mastered by the students. As the matter of fact, many students are still having difficulties due to the lack of vocabulary. According to Nurgiyantoro, picture card can be known as a good incentive to speak a foreign language in the early stage of learning. Therefore, this study then examines the issues which is concerning about the usage of the Quartett media as the media to improve the reproductive skill of speaking. Keywords : Quartett, vocabulary, skill of speaking